Faunal occurrence at naturally-forming waterholes in Shamwari Private Game Reserve, Eastern Cape, South Africa - Vowles, Kathleen Frances (My University, 2018)
This research examines the influence of surface water availability, which depends on rainfall, and temperature on faunal occurrence patterns at naturally-forming waterholes in Shamwari Private Game Reserve, Eastern Cape, South Africa. The objectives assess the occurrence and diversity of species at three naturally-forming waterholes and to examine the implications that rainfall and temperature have on species visitation patterns at naturally-forming waterholes. On a local scale, this research makes use of camera trap images activated by motion sensor, capturing at 10 second intervals to establish the faunal occurrence patterns and to determine wallowing activity of elephants, white rhino, and warthog at the waterholes over a short-time scale (June 2016 to November 2016). The frequencies of mammal species visiting times per hour were grouped into daily and monthly periods. Monthly data were examined, as this was a short-term study, hence shifts in faunal activity could be easily identified with local weather conditions monthly rather than seasonally (as seasonality was not the focus of the study). The occurrence of different species per hour at the waterholes was established over a period of six months (June to November). Distribution curves were created to determine species peak visitation times per hour, both daily and monthly, and pie charts were produced to determine shifts in individual species abundance each month. Local weather data were statistically analysed (Pearson`s correlation coefficient and cross-correlation) with faunal occurrence to determine the influence of these local weather conditions on faunal behaviour. Species-specific occurrences (daily and monthly) were established for all species that visited the three selected waterholes. Herbivore visitation occurred predominantly during diurnal hours and carnivores were observed during nocturnal hours. Temperature influenced species visitation times at these waterholes. As temperatures peaked (Tmax and Tmin), there was a decrease in species sighted at the waterholes. However, surface water availability, which is influenced by rainfall, was the crucial variable that drove faunal occurrence at the naturally-forming waterholes. More species were observed at the waterholes after rainfall events, compared to before rainfall. A delay in faunal occurrence was evident at the waterholes, two weeks after rainfall events. This lag exists due to the surface water, which was made available after rainfall events. Surface water availability and temperatures were, however, not the only factors that drove the occurrence of species at these waterholes. Other factors such as predator-prey relationships, tourist presence, cloud cover, inter- and intra-species competition, vegetation, soil type, and waterhole morphology influenced faunal occurrence patterns. iii Other objectives were to establish wallowing activity at the naturally-forming waterholes and to determine if there is a relationship between local weather variables and wallowing behaviour. As elephants, white rhino, and warthog are sparsely haired mammals, it is essential that they wallow for means of thermoregulation. Wallowing activity of these species only occurred during diurnal hours. In Shamwari at the three naturally-forming waterholes, warthogs wallowed more frequently than elephants and white rhino. Local weather variables influenced the wallowing behaviour of these species. An increase in temperature corresponded with an increase in wallowing activity. In addition, peak wallowing activity occurred at midday, when temperatures were at their highest. However, this depended on whether there was surface water available in these waterholes. A significant two week interval occurred between rainfall and wallowing activity (cross correlation function = 0.75), where the quantity of rainfall directly influenced the presence of surface water available in these waterholes. Without rainfall, the three naturally-forming waterholes remained dry and species did/could not undergo wallowing activity. It is essential to understand faunal visitation patterns and wallowing behaviour in relation to local weather variables, in particular with projected climate change scenarios. This study contributes to the knowledge necessary for the management decisions that ensure sustainability of wildlife in protected areas in South Africa. This can provide essential information for the construction of artificial waterholes, which should mimic natural waterholes and faunal distribution.
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for the degree of Masters of Science, University of the Witwatersrand, Johannesburg, 2018
Keywords: Water quality biological assessment--South Africa; Water quality management--South Africa; Water-supply--South Africa--Eastern Cape